Lysophosphatidic acid induces vasodilation mediated by LPA(1) receptors, phospholipase C, and endothelial nitric oxide synthase - Ruisanchez, Éva (Federation of American Societies for Experimental Biology, 2014)
Lysophosphatidic acid (LPA) has been implicated as a mediator of several cardiovascular functions, but its potential involvement in the control of vascular tone is obscure. Here, we show that both LPA (18:1) and VPC31143 (a synthetic agonist of LPA(1–3) receptors) relax intact mouse thoracic aorta with similar E(max) values (53.9 and 51.9% of phenylephrine-induced precontraction), although the EC(50) of LPA- and VPC31143-induced vasorelaxations were different (400 vs. 15 nM, respectively). Mechanical removal of the endothelium or genetic deletion of endothelial nitric oxide synthase (eNOS) not only diminished vasorelaxation by LPA or VPC31143 but converted it to vasoconstriction. Freshly isolated mouse aortic endothelial cells expressed LPA(1), LPA(2), LPA(4) and LPA(5) transcripts. The LPA(1,3) antagonist Ki16425, the LPA(1) antagonist AM095, and the genetic deletion of LPA(1), but not that of LPA(2), abolished LPA-induced vasorelaxation. Inhibition of the phosphoinositide 3 kinase–protein kinase B/Akt pathway by wortmannin or MK-2206 failed to influence the effect of LPA. However, pharmacological inhibition of phospholipase C (PLC) by U73122 or edelfosine, but not genetic deletion of PLCε, abolished LPA-induced vasorelaxation and indicated that a PLC enzyme, other than PLCε, mediates the response. In summary, the present study identifies LPA as an endothelium-dependent vasodilator substance acting via LPA(1), PLC, and eNOS.—Ruisanchez, É., Dancs, P., Kerék, M., Németh, T., Faragó, B., Balogh, A., Patil, R., Jennings, B. L., Liliom, K., Malik, K. U., Smrcka, A. V., Tigyi, G., Benyó, Z. Lysophosphatidic acid induces vasodilation mediated by LPA(1) receptors, phospholipase C, and endothelial nitric oxide synthase.